PENINGKATAN MOTIVASI REMAJA SMPN 1 GENDING GUNA MENGURANGI NILAI PERNIKAHAN DINI - Maksin, Mastina; Azzahra, Putri Fatimattus; Nafsiyah, Azizah Tun; Pratama, Vegas Albar; Nuraliza, Vadhea; Ningrum, Erika Fara Septia; Nasution, Hermawan (Universitas Mataram, 2024)
Teenagers are individuals between the ages of 12 and 18, and they are an important part of our society. Teenagers today face many challenges, including conflict problems and early marriage. Conflict can disrupt the learning process and make it difficult for students to concentrate and reach their full potential. Early marriage, on the other hand, can have broader negative consequences, including poorer health outcomes, lower employment opportunities, and lack of education. Early marriages that occur in Randupitu village are very high because many teenagers who marry are not yet old enough. This research uses the community service method with qualitative descriptive presentation. In order to clearly explain the implementation that has been carried out in the field. The research subject is the OSIS of SMPN 1 Gending which is located in Rondokuning, Randupitu, Gedning subdistrict, Probolinggo Regency. The implementation method is by holding outreach to provide motivation to students regarding the importance of education and early marriage by eliminating feelings of boredom in students. Providing motivation about the importance of education by eliminating feelings of boredom is an important achievement that can make it possible to minimize early marriage in Randupitu village. This activity emphasizes the importance of education for teenagers so they can plan a good future for their families and children. The OSIS of SMPN 1 Gending has recognized the role of teenagers in education by having principles and themselves in reducing feelings of excitement. The students know that these teenagers have a very important role in realizing the nation's ideals.